IBM TotalStorage Expert Hands-On Usage Guide - Lovelace, Mary; Cooper, John; Demer, Daniel; Schorm, Norbert (IBM Redbooks, 2003)
The IBM TotalStorage Expert V2R1 is the rebranded name for the IBM Storwatch Expert. It provides all the function in the StorWatch versions you have come to rely on - and then some. The IBM Total Storage Expert is made up of two component features: Enterprise Storage Server (ESS) Expert and Enterprise Tape Library (ETL) Expert. IBM TotalStorage Expert helps storage administrators boost the productivity of storage resources. It gathers and presents information that helps administrators manage the Enterprise Storage Server (ESS) and three Enterprise Tape Library (ETL) solutions: IBM TotalStorage Enterprise Automated Tape Library, IBM TotalStorage Virtual Tape Server, and IBM TotalStorage Peer-to-Peer Virtual Tape Server. The TotalStorage Expert prepares reports and graphical charts from the data it has collected. These reports and charts can be used in managing assets, capacity, and performance for your ESSs and ETLs. This IBM Redbooks publication will help you to install, tailor, and configure the TotalStorage Expert, and will show you how to use TotalStorage Expert.